Insider pledging: Its information content and forced sale - Chen, Hung-Kun; Hu, Shing-yang (Journal of Corporate Finance, 2024)
This paper investigates the information content of insider pledging and the forced sale of pledged shares using U.S. data. Contrary to warnings from proxy advisors and the media about insider pledging and suggestions for its prohibition, our findings show that insider pledging announcements do not negatively impact shareholder wealth. Firms with insider pledging experience positive one-year abnormal stock returns and higher future profitability after the disclosure of pledging, indicating that insider pledging signals a firm's better growth prospects. These positive abnormal returns observed after the disclosure of insider pledging are more pronounced in firms with better corporate governance and are associated with pledging by certain insiders with superior information. In addition, we find that the stock price does not significantly decline following the forced sale of pledged shares, indicating that the forced sale does not pose downside risks for shareholders. Overall, our results suggest that insider pledging is not detrimental to shareholder value in the U.S., contrary to findings reported in the literature on emerging markets.